Perbedaan perubahan berat badan, aktivitas fisik, dan kontrol glukosa darah antara anggota organisasi penyandang diabetes melitus dan non anggota - Isnawati, M.; Kurniawati, Dewi Marfuâ€™ah (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2016)
Background: Diabetes Mellitus (DM) is a metabolic disease that can not be cured, but the blood glucose levels can be controlled with diabetes management. There is organization in Indonesia for people with diabetes mellitus called Persadia (Persatuan Diabetes Indonesia). Patients who join diabetes peer group is expected to have a better lifestyle. Objective: To determine differences in weight changes, physical activity, and blood glucose control between Persadia members and non members.Method: Cross sectional study, with 42 subjects. The subjects were type 2 DM outpatients in Pantiwilasa Citarum Hospital, choosen by consecutive sampling and devided into 2 groups, Persadia members and non members. Weight changes was the difference of current weight with weight Â from 3 months ago. Physical activity was exercise habits and measured by questionnaire. Blood glucose control was glucose concentrations and measured by HbA1C examination. Statistical analysis used was Chi Square, Kolmogorov-Smirnov, and Fisher.Result: Persadia group members had more frequent physical activity (52.4%) than non-member groups (9.6%). Based on statistical analysis there is a difference of physical activity between Persadia group members and non members (p = 0,042). While on weight change (p = 0,537) and blood glucose control (p = 0,663) there was no difference between Persadia member and non member.Conclusion: There is a difference between Persadia members and non-members on physical activity. However, there was no difference in weight change and blood glucose control between Persadia and non-member members.